Study of cubic and hexagonal cell geometries of a 3D diamond detector with a proton micro-beam - Booth, MJ; Forcolin, GT; Grilj, V; Hamilton, B; Haughton, I; McGowan, M; Murphy, SA; Oh, A; Salter, PS; Sudić, I; Skukan, N (Elsevier, 2017)
A detector from single crystal synthetic diamond with conducting wires has been prepared with an improved femto-second laser process. The detector was characterised with a 4.5 MeV proton micro-beam (Ruđer Bos̆ković Institute, Zagreb). The charge collection efficiency and the transient current response have been investigated with high spatial resolution. A hexagonal and square cell geometry is investigated. Both cell geometries show full charge collection at 40 V bias voltage, and little charge sharing between neighbouring cells. The experimental data is compared to a simulation and qualitative agreement is observed.